# KSEEB Solutions for Class 8 Maths Chapter 2 Algebraic Expressions Ex 2.4

In this chapter, we provide KSEEB SSLC Class 8 Maths Chapter 2 Algebraic Expressions Ex 2.4 for English medium students, Which will very helpful for every student in their exams. Students can download the latest KSEEB SSLC Class 8 Maths Chapter 2 Algebraic Expressions Ex 2.4 pdf, free KSEEB SSLC Class 8 Maths Chapter 2 Algebraic Expressions Ex 2.4 pdf download. Now you will get step by step solution to each question.

## Karnataka Board Class 8 Maths Chapter 2 Algebraic Expressions Ex 2.4

Question 1.
Find the product:

i. (a + 3) ( a + 5)
ii. (3t + 1) (3t + 4)
iii. (a – 8) (a + 2)
iv. (a – 6) (a – 2)
i. (a + 3) (a + 5) This is in the form.
(x + a)(x + b) = x² + (a + b)x + ab
Here x = a, a = 3, b = 5
(a + 3)(a + 5) = a² + (a + 5)a + 3.5
= a² + 8a + 15

(ii) (3t + 1)(3t + 4)This is in the form.
(x + a)(x + b) = x² +(a + b)x + ab
Here x =3t,a = 1, b = 4
(3t – 1)(3t + 4) = (3t)²+(1 + 4)3t + 1.4
= 9t² + 5(3t) + 4 = 9t² + 15t + 4

(iii) (a -8)(a + 2)
This is in the form (x + a)(x + b) = x² + (a + b)x + ab
Here x = a, a = -8, b = 2
(a – 8)(a + 2) = a² + (-8 + 2)a + (-8)(2)
= a² + (-6)a – 16
= a² – 6a – 16

(iv) (a – 6)(a – 2)
This is in the form (x + a)(x + b) = x² +(a + b)x + ab
Herex = a, a = -6,b = -2
(a – 6)(a – 2) = a² + (- 6 – 2) a + (-6)(-2)
=a² + (- 8)a + 12
= a² – 8a + 12

2. Evaluate using suitable identities

Question i.
53 × 55
53 × 55 = (50 + 3) (50 + 5)
This is in the form (x + a)(x + b) = x² + (a + b)x + ab
Here x = 50, a = 3, b = 5
(50 + 3)(50 + 5) = 50² + (3 + 5) 50 + 3 × 5
= 2500 + (8)50 +15
= 2500 + 400 + 15
∴ 53 × 55 = 2915

Question ii.
102 × 106
102 × 106 = (100 + 2) (100 + 6) This is in the form.
(x + a)(x + b) = x² +(a + b)x + ab
Here x = 100, a = 2, b = 6
(100 + 2)(100 + 6) = 100² +(2 + 6)100 + 2 × 6
= 10000 + (8)100 + 12
= 10000 + 800 + 12
∴102 × 106 = 10812

Question iii.
34 × 36
34 × 36 = (30 + 4) (30 + 6) This is in the form.
(x + a)(x + b) = x²+ (a + b)x + ab
Here x =30, a = 4, b = 6
(30 + 4)(30 + 6) = 30² + (4 + 6)30 + 4 × 6
= 900 + 300 + 24
34 × 36 = 1224

Question iv.
103× 96
Answer: 103 × 96 = (100 + 3)(100-4)This is in the form.
(x + a)(x + b) = x² + (a + b)x + ab
Here x = 100,a = 3,b = -4 (100 + 3)(100-4) = 100² + (3 – 4)100 + 3 × -4
= 10000 + (- 1)100 – 12
= 10000 – 100 – 12
103 × 96 = 9888

Question 3.
Find the expression for the product (x+a) (x+b) (x+c) using the identity (x+a)(x+b) = x² + (a + b)x + ab
(x + a) (x + b) (x + c)
Consider (x + a)(x + b)
= x² + (a + b)x + ab
= x² + ax + bx + ab (x + a)(x + b)(x + c)
= (x² + ax + bx + ab)(x + c)
= x(x² + ax + bx+ ab) + c
(x² + ax + bx + ab)
= x3 + ax² + bx² + abx + cx² + cax +cbx + abc
= x3 + ax² + bx² + cx² + abx + cax +cbx + abc [by rearranging]
= x3 + x²(a + b + c) + x(ab + ca +bc) + abc
∴ (x + a)(x + b)(x + c)
= x3 +x² (a + b + c) + x(ab + bc + ca) + abc

4. Using the identify (a+b)2 = a² + 2ab+b² simplify the following.

Question i.
(a + 6 )²
Using the identity
(a + b)² = a² + 2ab + b²
(a + 6)² = a² +2.a.6 + 6²
= a² +12a + 36

Question ii.
(3x+2y)2
Using the identity
(a + b)² = a² +2ab + b²
(3x + 2y)² =(3x)² + 2.3x.2y + (2y)²
= 9x² +12xy + 4y²

Question iii.
(2p + 3q)²
Using the identity
(a + b)² =a² + 2ab + b²
(2p + 3q)² =(2p)² +2.2p.3q + (3q)²
= 4p² + 12pq + 9q²

Question iv.
(x² + 5)²
Using the identity (a + b)² = a² +2ab + b²
(x² +5)² = (x²)² + 2.x².5 + 52 = x4 + 10x² + 25

5. Evaluate using the identity (a+b)² = a² + 2ab + b²

Question i.
(34)²
34² = (30 + 4)²
(a + b)² = a² + 2ab+ b² Here a = 30, b = 4
(30 + 4)² = (30)² + 2 × 30 × 4 + (4)²
= 900 + 240 + 16
(34)² = 1156

Question ii.
(10.2)²
(10.2)² = (10 + 0.2)²
(a + b)² = a² + 2ab + b² Here a = 10, b=0.2
[(10 + (0.2))]² = 10² +2.(10).(0.2) + (0.2)² ]
= 100 + 4 + 0.04
(10.2)² = 104.04

Question iii.
53²
53² = (50 + 3)²
(a + b)² =a² +2ab + b²
Here a = 50, b = 3 (50 + 3)² =50² + 2 × 50 × 3 + (3)²
= 2500 + 300 + 9
53² = 2809

Question iv.
(41 )²
41² = (40 + 1)²
(a + b)² = a² + 2ab + b²
Here a = 40,b = 1
(40 + 1)² = 40² + 2 × 40 × 1 + (1)²
= 1600 + 80 + 1
41² = 1681

6. Use the identify (a -b)² = a² – 2ab + b² to compute.

Question i.
(x – 6)²
(a – b)² = a² – 2ab + b²
Herea = x, b=6
(x – 6)² = x² – (2)(x)(6) + 6²
= x² – 12x+ 36

Question ii.
(3x – 5y)²
(a – b)² = a² – 2ab + b² Here a = 3x, b = 5y
(3x – 5y)² = (3x)² -(2)(3x)(5y) + (5y)² = 9x² – 30xy + 25y²

Question iii.
(5a – 4b)²
(a – b)² = a² – 2ab + b²
Here a = 5a, b = 4b
(5a – 4b)² = (5a)² – (2)(5a)(4b) + (4b)²
= 25a² – 40ab + 16b²

Question iv.
(p² – q²)²
(a – b)² = a² – 2ab + b² Here a = p² , b = q2
(p² – q²)² = (p²)² – (2)(p²)(q²) + (q²)²
= p4 – 2p²q² + q4

7. Evaluate using the identify (a – b)² = a² – 2ab + b².

Question i.
(49)²
49² = (50 – 1)²
(a – b)² = a² – 2ab + b² Here a = 50, b = 1
(50 – 1)² = 50² – (2)(50)(1) + 1² = 2500 – 100 + 1
(49)² = 2401

Question ii.
(9.8)²
(9.8)² = (10 – 0.2)²
(a – b)² =a² – 2ab + b² Here a = 10, b=0.2
(10 – 0.2)² = 10² – (2)(10)(0.2) + (0.2)²
= 100 – 4 + 0.04
(9.8)² =96.04

Question iii.
59²
59² = (60 – 1)²
(a – b)² = a² – 2ab + b² Here a = 60, b = 1
(60 – 1)² = 60² – (2)(60)(1) +12 = 3600 – 120 + 1
59² =3481

Question iv.
(198)²
(198)² = (200 – 2)²
(a – b)² = a² – 2ab + b² Here a = 200, b = 2
(200 – 2)² = 200² – (2)(200)(2) + 2²
= 40000 – 800 + 4
(198)² = 39204

8. Use the identify (a + b) (a – b) = a² – b² to find the product.

Question i.
(x + 6) (x – 6)
(a + b) (a – b) = a2 – b2
Here a = x,b = 6
(x + 6)(x – 6) = x² – 6² = x² – 36

Question ii.
(3x + 5) (3x – 5)
(a + b) (a – b) = a² – b²
Here a = 3x, b = 5
(3x + 5)(3x – 5) = (3x)² – (5)²
= 9x² -25

Question iii.
(2a + 4b) (2a – 4b)
(a + b) (a – b) = a² – b²
Here a = 2a,b = 4b
(2a + 4b)(2a-4b) = (2a)² – (4b)²
= 4a² – 16b²

Question iv.
(2×3+1)(2×3−1)
(a + b) (a – b) = a² – b²
Here a = 2×3 ,b = 1
(2×3+1)(2×3−1) = (2×3)2−12
= 4×29−1

9. Evaluate these using identity :

Question i.
55 × 45
55 × 45 = (50 + 5) (50 – 5)
Identity (a + b)(a – b) = a² – b²
Here a = 50,b=5
(50 + 5)(50 – 5) = (50)² – 5²
= 2500 – 25
55 × 45 = 2475

Question ii.
33 × 27
33 × 27 = (30 + 3) (30 – 3)
identity (a + b)(a – b) = a² – b²
Here a = 30,b = 3
(30 + 3)(30 – 3) = 30² – 3² = 900 – 9
33 × 27 = 891

Question iii.
8.5 × 9.5
8.5 × 9.5 = (9 – 0.5) (9 + 0.5)
Here a = 9, b = 0.5
(9 – 0.5)(9 + 0.5) = (9²) – (0.5)² = 81 – 0.25
= 80.75

Question iv.
102 × 98
102 × 98 = (100+ 2) (100 – 2)
Identity (a + b)(a – b) = a2 – b2
Here a = 100, b= 2
(100 + 2)(100 – 2) = 100² – 2² =10000 – 4
102 × 98 = 9996

10. Find the product.

Question i.
(x – 3)(x + 3) (x2 + 9)
(x – 3)(x + 3) (x2 + 9)
Identity(a + b)(a-b) = a² – b²
= (x² – 3²)(x² + 9)
= (x² – 9)(x² + 9)
= (x²)² – 9²
= x4 – 81

Question ii.
(2a + 3)(2a – 3) (4a² + 9)
(2a + 3)(2a – 3) (4a² + 9)
Identity (a + b)(a-b) = a² – b²
= [((2a)² – 3²)(4a²+9)²
= (4a² – 9)(4a² + 9)
= (4a²)² – 9² = 16a4 – 81

Question iii.
(P + 2) (P – 2) (P² + 4)
(P + 2) (P – 2) (P² + 4)
Identity (a + b)(a – b) = a² – b²
= (P² – 2²)(P²+ 4)
= (P² – 4)(P² + 4)
= (P²)² – 4² = P4 – 16

Question iv.
(12m−13)(12m+13)(14m2+19)

Question v.
(2x – y)(2x + y) (4x² + y²)
(2x – y)(2x + y) (4x² + y²)
Identity (a + b)(a – b) = a² – b²
[(2x)² – y²](4x² + y²)
= (4x² – y²)(4x² + y²)
= I6x4 – y4

Question vi.
(2x – 3y)(2x + 3y) (4x² + 9y²)
(2x – 3y)(2x + 3y) (4x² + 9y²)
Identity (a + b)(a-b) = a² -b²
= [(2x)² – (3y)²](4x²+ 9y²)
= (4x² – 9y²)(4x² + 9y²)
= (4x²)² – (9y²)²
= 16x4 – 81y4

All Chapter KSEEB Solutions For Class 8 maths

—————————————————————————–

All Subject KSEEB Solutions For Class 9

*************************************************

I think you got complete solutions for this chapter. If You have any queries regarding this chapter, please comment on the below section our subject teacher will answer you. We tried our best to give complete solutions so you got good marks in your exam.

If these solutions have helped you, you can also share kseebsolutionsfor.com to your friends.

Best of Luck!!